(I)literate identities in adult basic education: a case study of a latino woman in an ESOL and computer literacy class - Jiménez, Juan Pablo (Colombian Applied Linguistics Journal, 2007)
Adult Basic Education (ABE), namely English to Speakers of Other Languages (ESOL) in the United States has been understood and assessed as the mastering of skills increasingly aimed at meeting the demands of the workplace. This ethnographic case study examines how the literacy practices a Latino woman engages in through her participation in an ABE-ESOL class relate to her developing identities of mother, student and citizen. Using Critical Discourse Analysis (CDA), the findings demonstrate the contextual nature of adult literacy, showing how learners appropriate available tools and texts and enact purposeful and meaningful literacy practices, which traditional ABE assessment dismiss or do not account for. Implications for adult literacy pedagogy and research are discussed.